Adhesion Strength of Multi-element Coatings of the System (TiNbCrZrSi)N - U.S. Nyemchenko; V.Yu. Novikov; S.S. Grankin; V.V. Ganenko; M.Yu. Arseenko; O.V. Sobol; O.P. Tkach; M.G. Kovaleva; L.V. Malikov (Журнал нано- та електронної фізики)
The mechanical characteristics of the multi-element coatings (TiNbCrZrSi)N have been studied depending on the deposition process parameters, in particular the bias potential. X-ray diffraction spectra has shown, that the coating is formed on the basis of single-phase state of the fcc lattice, which in the case of nitrides has structural type NaCl. Hardness and elastic modulus of the coating (TiNbCrZrSi)N varies from H = 24 GPa and E = 254 GPa to H = 28.9 GPa and E = 291 GPa. Coatings’ index of resistance to plastic deformation (H3/E2) has a value of 0.28.